ANALISIS FAKTOR KEUANGAN DAN NON KEUANGAN YANG MEMPENGARUHI PERINGKAT OBLIGASI - Susanti - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2015)
Bond rating is something that should be considered for investors and issuers of bonds priorto making an investment decision. Bond Ratings provide an informative statement and signals abouta possible failure of a company's debt. The aim of this study is to provide empirical evidence onfinancial and non-financial factors which allegedly can predict bond ratings. On financial factors usedleverage ratios, profitability and the size of the company, while non-financial factors used bond age